2019
DOI: 10.1016/j.cpletx.2019.100037
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-chemical theory for anion hydration and specific ion effects:Cl-(aq) vs.F-

Abstract: Anion hydration is complicated by H-bond donation between neighboring water molecules in addition to H-bond donation to the anion. This situation can lead to competing structures for chemically simple clusters like (H 2 O) n Cl − and to anharmonic vibrational motions. Quasi-chemical theory builds from electronic structure treatment of isolated ion-water clusters, partitions the hydration free energy into inner-shell and outer-shell contributions, and provides a general statistical mechanical framework to study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 123 publications
(196 reference statements)
5
55
0
Order By: Relevance
“…Therefore, it may not be very surprising that the stability of the water wire in gA is not optimally modeled by these water models. Recent ab initio MD simulations have shown that, while interacting with a chloride ion, the water dipole flips rapidly on the picosecond timescale, but, with a fluoride ion where the proton approaches more closely, the water dipole becomes stable (50). This work hints that a quantum treatment of the water wire in the gA pore, where waters are restricted in orientation to form strong interactions with carbonyls, may have a much longer lifetime than in the classical MD simulations.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, it may not be very surprising that the stability of the water wire in gA is not optimally modeled by these water models. Recent ab initio MD simulations have shown that, while interacting with a chloride ion, the water dipole flips rapidly on the picosecond timescale, but, with a fluoride ion where the proton approaches more closely, the water dipole becomes stable (50). This work hints that a quantum treatment of the water wire in the gA pore, where waters are restricted in orientation to form strong interactions with carbonyls, may have a much longer lifetime than in the classical MD simulations.…”
Section: Resultsmentioning
confidence: 92%
“…The polar character of water leads to the dissociation of salts in aqueous solution and the dispersion of the resulting ions. The solvation of anions through hydrogen bonding in aqueous solution [2] has been investigated theoretically for a number of anions [3,4], including Fand Cl - [5][6][7][8][9], BF 4 - [10] and PF 6 - [11]. Among the myriad of possible anions, we have turned our attention to BeF 3 -1 and BeF 4 -2 .…”
Section: Introductionmentioning
confidence: 99%
“…Important aspects of those mecha-23 nisms in aqueous solution involves the local ion hydration properties, and exchange of 24 hydrating water molecules for molecular ligating groups [3,5,[10][11][12]. As a step toward 25 enhancing our understanding of ion-specific effects, this paper studies the structures 26 and free energies of hydration clusters of the anions F − , Cl − , Br − , and I − in the dilute 27 gas-phase, with the longer term goal of addressing the comparative behavior of this se-28 ries of ions in liquid water on the basis of quasi-chemical theory (QCT) [12][13][14][15]. Accurate 29 characterization of gas-phase clusters can indeed helpfully inform QCT applications, 30 and has been successful for cations [12].…”
Section: Introduction 17mentioning
confidence: 99%
“…We compared: i) the experimental values determined from mass spectrometry [45]: ii) 85 the quantum-mechanical rigid rotor harmonic oscillator approximation (Figure 1), and 86 iii) the rough-energy landscape procedure proposed in Ref [15]. Figure 2 summarizes all 87 results graphically.…”
mentioning
confidence: 99%
See 1 more Smart Citation